HISTORICAL CONSIDERATIONS ON THE EVOLUTION OF GYNECOLOGY - Graña, Alejandro (2015)
One of the biggest problems for scientific observation of the female genitalia was always finding the method to achieve look inside the vaginal cavity. And although some forms of what we now call speculum were known to the Egyptians and the Hebrews, and developed forms of it have been found in Pompeii, later also they were used by Galen (11th century) and the Arab Albucasis (1085).